Structural Basis for Complement Evasion by Lyme Disease Pathogen Borrelia burgdorferi - Bhattacharjee, Arnab (American Society for Biochemistry and Molecular Biology, 2013)
Borrelia burgdorferi spirochetes that cause Lyme borreliosis survive for a long time in human serum because they successfully evade the complement system, an important arm of innate immunity. The outer surface protein E (OspE) of B. burgdorferi is needed for this because it recruits complement regulator factor H (FH) onto the bacterial surface to evade complement-mediated cell lysis. To understand this process at the molecular level, we used a structural approach. First, we solved the solution structure of OspE by NMR, revealing a fold that has not been seen before in proteins involved in complement regulation. Next, we solved the x-ray structure of the complex between OspE and the FH C-terminal domains 19 and 20 (FH19-20) at 2.83 Å resolution. The structure shows that OspE binds FH19-20 in a way similar to, but not identical with, that used by endothelial cells to bind FH via glycosaminoglycans. The observed interaction of OspE with FH19-20 allows the full function of FH in down-regulation of complement activation on the bacteria. This reveals the molecular basis for how B. burgdorferi evades innate immunity and suggests how OspE could be used as a potential vaccine antigen.